Analysis of Evacuation Route and Fire Safety in Main Library University Building - Fira Rahmawati; Noor Cholis Idham; Rania Ababssi (Universitas Sebelas Maret Surakarta, 2025)
Fire safety is a major concern in public buildings, especially in educational institutions with high user density and complex layouts. The Main Library of Universitas Islam Indonesia (UII) must be prepared to handle emergencies through well-planned evacuation routes. This study analyzes the existing evacuation system and fire safety conditions in the library. Using Pathfinder simulation software, the research models pedestrian behavior during evacuation to assess time efficiency, congestion points, and overall route effectiveness. Key factors include exit accessibility, user familiarity, crowd density, and pathway dimensions. The simulation reveals issues such as limited stairwell capacity, poorsignage visibility, and inadequate alternative routes.This study recommends improving exit width, repositioning emergency signs, and conducting regular evacuation drills. These interventions aim to enhance evacuation safety and align with national fire safety standards, contributing to a safer and more resilient academic environment.